Chemical Constituents and Antimicrobial and Antioxidant Activities of Essential Oil from Dried Seeds of Xylopia aethiopica - Samba Fama Ndoye; Yoro Tine; Insa Seck; Lalla Aicha Ba; Seydou Ka; Ismaila Ciss; Abda Ba; Seynabou Sokhna; Moussa Ndao; Rokhaya Sylla Gueye; Nango Gaye; Abdoulaye Diop; et al. (Biochemistry Research International)
The study aimed to investigate the chemical composition and antimicrobial and antioxidant activities of the essential oil from dried seeds of Xylopia aethiopica. The essential oil was obtained by hydrodistillation and analyzed by GC/FID and GC/MS. The essential oil yield was 1.35%. Forty-nine compounds were identified in the essential oil with 1,8-cineole (16.3%), β-pinene (14.8%), trans-pinocarveol (9.1%), myrtenol (8.3%), α-pinene (5.9%), and terpinen-4-ol (5.6%) as major components. The antimicrobial activity of this essential oil was studied using disk diffusion and broth microdilution methods on four bacteria (Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Pseudomonas aeruginosa) and one fungus (Candida albicans). The essential oil exhibited excellent activity against S. aureus, E. faecalis, and C. albicans and moderate activity against E. coli. Among all strains tested, C. albicans showed the best sensitivity with a MIC of 50 mg/mL. The antioxidant activity was examined using a DPPH-free radical scavenging assay. The essential oil of X. aethiopica showed low antioxidant activity (IC50 = 784.604 ± 0.320 mg/mL) compared to that of ascorbic acid and the reference compound (IC50 = 0.163 ± 0.003 mg/mL). The results indicate that consumption of X. aethiopica seeds can reduce the virulence of food-borne pathogens and their resistance to antibiotics.